The predictability of heat-related mortality in Prague, Czech Republic, during summer 2015-a comparison of selected thermal indices - Urban, Aleš; Hondula, David M; Hanzlíková, Hana; Kyselý, Jan (International journal of biometeorology, 2019)
We compared selected thermal indices in their ability to predict heat-related mortality in Prague, Czech Republic, during the extraordinary summer 2015. Relatively, novel thermal indices-Universal Thermal Climate Index and Excess Heat Factor (EHF)-were compared with more traditional ones (apparent temperature, simplified wet-bulb globe temperature (WBGT), and physiologically equivalent temperature). The relationships between thermal indices and all-cause relative mortality deviations from the baseline (excess mortality) were estimated by generalized additive models for the extended summer season (May-September) during 1994-2014. The resulting models were applied to predict excess mortality in 2015 based on observed meteorology, and the mortality estimates by different indices were compared. Although all predictors showed a clear association between thermal conditions and excess mortality, we found important variability in their performance. The EHF formula performed best in estimating the intensity of heat waves and magnitude of heat-impacts on excess mortality on the most extreme days. Afternoon WBGT, on the other hand, was most precise in the selection of heat-alert days during the extended summer season, mainly due to a relatively small number of "false alerts" compared to other predictors. Since the main purpose of heat warning systems is identification of days with an increased risk of heat-related death rather than prediction of exact magnitude of the excess mortality, WBGT seemed to be a slightly favorable predictor for such a system.
Keywords: Wind; Cities; vlhkost; roční období; Heat Stress Disorders; Humans; Česká republika; Models, Theoretical; lidé; vítr; velkoměsta; teoretické modely; poruchy vyvolané tepelným stresem; vysoká teplota; Seasons; Hot Temperature; Czech Republic; Humidity